Modern Diagnostic Approaches in Celiac Disease: Molecular Mechanisms, Biomarkers and Emerging Technologies - Szamocka, Karolina; Strzewiczek, Aleksandra (Quality in Sport, 2026)
Introduction Celiac disease is a chronic autoimmune disorder triggered by gluten in genetically predisposed individuals. Incomplete digestion of gluten leads to immunogenic peptides that activate intestinal immune responses, causing inflammation and damage to the small intestinal mucosa. Early and accurate diagnosis is crucial to prevent complications such as malabsorption, anemia, osteoporosis, and neurological disorders. Aim of the Study This review aims to summarize current and emerging diagnostic methods for celiac disease, with a focus on biochemical mechanisms, molecular biomarkers, and advanced laboratory techniques, including proteomics, microRNA profiling, and nanotechnology-based biosensors. Materials and Methods A literature review was conducted using PubMed to identify studies on celiac disease diagnostics, molecular mechanisms, and biomarkers. Peer-reviewed clinical studies, systematic reviews, and experimental research were analyzed to provide a comprehensive overview of current knowledge and innovative diagnostic approaches. Conclusion Modern diagnostics combine serological, genetic, and histopathological methods, with key biomarkers such as anti-tissue transglutaminase and deamidated gliadin peptide antibodies linked to disease mechanisms. Emerging technologies like proteomics, microRNA analysis, metabolomics, and nanotechnology-based biosensors offer promising tools for early, sensitive, and non-invasive detection, improving disease monitoring and patient care.